QPSK Training Sequence-Based Both OSNR and Chromatic Dispersion Monitoring in DWDM Systems - Feilong Wu; Aiying Yang; Peng Guo; Yaojun Qiao; Lingwei Zhuang; Shaojian Guo (IEEE Photonics Journal)
We design a quadrature phase-shift keying training sequence (QPSK-TS) for monitoring both optical signal-to-noise ratio (OSNR) and chromatic dispersion (CD) in a dense wavelength division multiplexing (DWDM) system. By applying fast Fourier transform on the QPSK-TS, a comb-like spectrum with discrete peaks can be obtained. OSNR can be calculated by measuring the power of the amplified spontaneous emission (ASE) noise in the gaps between these peaks. Moreover, we search the optimal order in the fractional domain to calculate the CD after applying fractional Fourier transform on the QPSK-TS signal. The proposed method shows large ASE noise and optical nonlinearity tolerance in simulation results ( $<$ 1.0 dB error within 24 dB after transmission over 1000 km with 3 dBm per channel launch power, and $<$ 90 ps/nm error within 33400 ps/nm). Furthermore, the experimental results demonstrate high accuracy of the proposed method ( $≤$ 1.0 dB error within 28 dB and $<$ 40 ps/nm error within 1670 ps/nm after 100 km single channel transmission).